From street corner to smartphone: assessing the prospects of socio-technical transitions in Cape Town's transport sector - Alexander, Christian (School of Architecture, Planning and Geomatics, 2025)
Workers, employers, shoppers, students, businesses, institutions, and governments share a problem in Cape Town: how to get around. Individuals bear this problem, but its consequences reverberate at a broader level, affecting economic security, social stability, and environmental sustainability. The city's spatial composition, an institutional legacy of socio-economic and racial exclusion, an over-reliance on private automobiles, and underinvestment in public transport are all commonly-cited culprits. Stakeholders are less unified in identifying solutions. Infrastructure- and technology-led approaches, such as new Bus Rapid Transit and technology-enabled on-demand services, are making their entry into the transport arena, but it is unclear how they will interact with established systems, such as the minibus taxi paratransit service. Furthermore, these approaches suggest a perpetuation of modernist tendencies towards techno-determinism. This research focused on the transport travails of one location in Cape Town in order to better understand how new technologies and innovations might impact access and mobility there. The location, a new University of Cape Town (“UCT”) satellite facility at a place known as Philippi Village, provided a practical vantage point from which to learn more about the dynamics at play in Cape Town's transportation ecosystem. Applying a sociotechnical approach known as Actor-Network Theory (“ANT”), I describe the various actors and relationships that enable access to this location. These descriptions reveal six insights: the central role of the road and private automobile actor-networks in conceptualising how the site should be accessed; the high influence of crime on how access is viewed and resolved; the varied transport needs of users; the benefits of passenger agency; the poor integration of public transport modes; and the divergence between existing and new transport actor-networks in actors enrolled and mobilised. From these insights I describe a range of proposals that Philippi Village users, UCT actors, and others might pursue in order to address their transportation issues. Beyond these direct proposals, I discuss ANT's usefulness as a tool for city planning, and highlight some of the larger lessons regarding Cape Town's orientation around car-centric development.